Remote monitoring of implantable loop recorders reduces time to diagnosis in patients with unexplained syncope: a multicenter propensity score-matched study - Russo, Vincenzo; Rago, Anna; Grimaldi, Nicola; Chianese, Raffaele; Viggiano, Aniello; D’Alterio, Giuliano; Colonna, Diego; Mattera Iacono, Agostino; Papa, Andrea Antonio; Spadaro Guerra, Andrea; Gargaro, Alessio; Rapacciuolo, Antonio; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background There are little data on remote monitoring (RM) of implantable loop recorders (ILRs) in patients with unexplained syncope and whether it confers enhanced diagnostic power. Objective To evaluate the effect of RM in ILR recipients for unexplained syncope for early detection of clinically relevant arrhythmias by comparison with a historical cohort with no RM. Methods SyncRM is a propensity score (PS)-matched study prospectively including 133 consecutive patients with unexplained syncope and ILR followed up by RM (RM-ON group). A historical cohort of 108 consecutive ILR patients with biannual in-hospital follow-up visits was used as control group (RM-OFF group). The primary endpoint was the time to the clinician's evaluation of clinically relevant arrhythmias (types 1, 2, and 4 of the ISSUE classification). Results The primary endpoint of arrhythmia evaluation was reached in 38 patients (28.6%) of the RM-ON group after a median time of 46 days (interquartile range, 13–106) and in 22 patients (20.4%) of the RM-OFF group after 92 days (25–368). The PS-matched adjusted ratio of rates of arrhythmia evaluation was 2.53 (95% confidence interval, 1.32–4.86) in the RM-ON vs. RM-OFF group (p = 0.005). Conclusion In our PS-matched comparison with a historical cohort, RM of ILR patients with unexplained syncope was associated with a 2.5-fold higher chance of evaluations of clinically relevant arrhythmias as compared with biannual in-office follow-up visits.